Denomination of origin Penedés: an historic, geographic and wine tourism context - Molleví, Gemma; Miró, Albert (Geographicalia, 2018)
The Penedés Designation of Origin, a region located between Barcelona and Tarragona, is the most important in Catalonia in terms of size and production. Its history and viticulture heritage are very old and of great wealth. Thus, this research work focuses on a dual objective, on the one hand is to contrast the hypothesis of the existence of a positive relationship between the total number of wine companies and total production, in hectoliters, and secondly in recent years There is a common interest to protect its viticulture landscape. That is why the Penedés Landscape Charter has been drawn up, which is postulated to be a World Heritage Site by UNESCO. Under these circumstances, the public and private institutions of Penedés intend to convert the D.O. Penedés in Qualified Denomination of Origin, also to achieve this goal is working to promote quality wine tourism efficiently.